Splenic abscess: a rare presentation - Mohit Bhatia; Hanumant Lohar; Daksha S Nirhale; Vishal Tomar (The Egyptian Journal of Internal Medicine, 2015)
Splenic abscess is a rare clinical entity with an incidence of 0.2-0.7% in autopsy-based studies. When untreated, splenic abscess is associated with nearly 100% mortality; in treated patients, the mortality rate is 16.6% during the first 90 days. It mostly occurs in patients with neoplasia, immunodeficiency, trauma, diabetes or splenic infarct. The incidence of splenic abscess is thought to be growing because of the increase in the number of immunocompromised patients who are particularly at risk for this disease and also because of the widespread use of diagnostic modalities. However, the optimal treatment for this remains unclear. We present a case of a 42-year-old man diagnosed with multiloculated splenic abscess and was subjected to splenectomy.